1983
DOI: 10.1111/j.1600-0447.1983.tb06728.x
|View full text |Cite
|
Sign up to set email alerts
|

Studies on biogenic amine metabolizing enzymes (DBH, COMT, MAO) and pathogenesis of affective illness

Abstract: Erythrocyte COMT activity was determined in 31 healthy persons (16 men, 15 women) and in 34 persons with endogenous depressive syndrome (12 men, 22 women). It was found that enzyme activity is significantly higher in healthy men than in healthy women. In the group of women with endogenous depressive syndrome COMT activity is elevated as compared with the group of healthy women (P less than 0.05). This is true of all forms of affective disease: bipolar, unipolar, and undifferentiated. High COMT activity in wome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

1984
1984
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…Because of its role in catecholamine metabolism, COMT enzymatic activity has previously been measured in the peripheral blood of patients with mood disorders and schizophrenia. However, the results of these studies have been equivocal [Dunner et al, 1977;Philippu et al, 1981;Puzynski et al, 1983;Karege et al, 19871.…”
Section: Resultsmentioning
confidence: 93%
“…Because of its role in catecholamine metabolism, COMT enzymatic activity has previously been measured in the peripheral blood of patients with mood disorders and schizophrenia. However, the results of these studies have been equivocal [Dunner et al, 1977;Philippu et al, 1981;Puzynski et al, 1983;Karege et al, 19871.…”
Section: Resultsmentioning
confidence: 93%
“…As a first step toward understanding the consequences of the absence of COMT on neurotransmission in several brain regions, steady-state levels of dopamine and norepinephrine were compared in the striatum, frontal cortex, and hypothalamus of homozygous and wild-type animals. Based on our previous observations, which suggested a sexually dimorphic contribution of COMT in psychiatric phenotypes (10), as well as on earlier observations by others (12), male and female animals were analyzed separately (Fig. 3).…”
Section: Resultsmentioning
confidence: 99%
“…Studies on the comt allele distribution, as well as extensive mutational analysis failed to reveal a major effect of low COMT activity on schizophrenia (9), although studies on case͞control samples (10) and more recently affected families (M.K., C. A. Sobin, M. L. Blundell, B. L. Galke, L. Malinova, P. Goldberg, J. Oh, and J.A.G., unpublished results) suggested that the low activity allele of this gene is significantly associated with susceptibility to OCD in a recessive and sexually dimorphic manner. In addition, earlier studies assaying enzyme activity suggested a sexually dimorphic role for this gene in affective disorder (11,12), an observation supported by more recent studies using genetic markers (13). The involvement of COMT in the monoamine metabolic pathways could explain the pleiotropic effect of this gene on susceptibility to psychiatric disorders and symptoms.…”
mentioning
confidence: 76%
“…Monoamine oxidase, the enzyme responsible for the degradation of both catecholamines and 5‐HT, could be one of the mediating factors in the aetiology of depression associated with ageing 25 . There are two subtypes of MAO, namely MAO‐A and MAO‐B, in rat brain 26 .…”
Section: Discussionmentioning
confidence: 99%